After annie eaudiobook A novel. - Quindlen, Anna (Books on Tape, 2024)
NEW YORK TIMES BESTSELLER • “Part of Quindlen’s gift is that you don’t just read about these characters, you inhabit them. . . . Luminous with life, hope and the power of love.”— People (A Book of the Week Pick) “[A] quietly revelatory and gently gleaming gem of a book.”— The New York Times Book Review (Editors’ Choice) Anna Quindlen’s trademark wisdom on family, friendship, and the ties that bind us are at the center of this novel about the power of love to transcend loss and triumph over adversity, by the author of Still Life with Bread Crumbs and One True Thing . When Annie Brown dies suddenly, her husband, her children, and her closest friend are left to find a way forward without the woman who has been the lynchpin of all their lives. Bill is overwhelmed without his beloved wife, and Annemarie wrestles with the bad habits her best friend had helped her overcome. And Ali, the eldest of Annie’s children, has to grow up overnight, to care for her younger brothers and even her father and to puzzle out for herself many of the mysteries of adult life. Over the course of the next year what saves them all is Annie, ever-present in their minds, loving but not sentimental, caring but nobody’s fool, a voice in their heads that is funny and sharp and remarkably clear. The power she has given to those who loved her is the power to go on without her. The lesson they learn is that no one beloved is ever truly gone. Written in Quindlen’s emotionally resonant voice and with her deep and generous understanding of people, After Annie is about hope, and about the unexpected power of adversity to change us in profound and indelible ways.